Numbered Heads Together (NHT) of Cooperative Model for Improving Student’s Geography Study Result in X2 Class SMA NEGERI 2 Watangsoppeng - Hariana, Hilda Cahyani; Zhiddiq, Sulaiman; Baharuddin, Ichsan Invanni (Universitas Negeri Makassar, 2018)
This study aimed to assess whether NHT cooperative learning model to improve learning outcomes of students geography. Implementation of the actions performed by 2 cycles, each cycle consists of planning, action, observation and evaluation, and reflection. Analysis using quantitative descriptive analysis. The results showed that: there is an increase in learning outcomes for implementing cooperative learning model NHT during the execution of the learning cycle I and xycle II. The everage value of the learning outcomes before deploying cooperative learning model NHT increased 68,09 after applied cooperative learning model NHT, in the first cycle is obtained mean values obtained by an average of 76,26. It can be concluded that through the application of learning models on the subjects geography of NHT can improve student learning outcomes geography class X2 SMAN 2 Watansoppeng..